Bridging the Divide: A critical analysis of intercultural dialogue through videoconference as a Peace Education Practice - FABRIS, BARRET (Trinity College Dublin. School of Religions,Theology & Ecumenics. Irish School of Ecumenics, 2018)
'Building Bridges: A Critical Examination of the Use of Videoconference as a Peace Education Practice' focuses on whether intercultural dialogue though videoconference is a viable means of supporting processes of conscientization, thereby, defining videoconference as a peace education practice. In order to effectively assess videoconference as a peace education practice a critical understanding of the field of peace education required the construction of a model, which is based upon an extensive literature review of peace education. The model, subsequently, defines the researcher's understanding of the field and the means in which to design and assess subsequent practices. The Three Sphered Model of Peace Education argues that peace education is defined by a human agency informed by critical pedagogy, a constructivist epistemol ogy, and a cosmopolitan normative approach. This understanding enables a critical examination of videoconference and a more thorough appreciation of what defines dialogue within a peace education practice. Videoconference based activities have been utilized by schools worldwide through a variety of different mediums. However, such practices have had little assessment, and while the potential of videoconference to overcome geographical boundaries and facilitate intercultural dialogue presents powerful potential, it has not been determined whether such initiatives can support students and teachers to adopt a consciousness of peace or the support the continuation of bias, stereotypes, and isolation. In order to effectively address this dilemma this study collaborated with Global Nomads Group and Bridges of Understanding to examine their Youth Talk Program. Youth Talk connects students from the United States and the MENA over the course of a school year through virtual exchanges. By conducting virtual and on - site focus groups, interviews, and observations , key distinctions were found in the power dynamics, purpose, and outcomes between partnered schools. Through the application of the Three Sphered Model of Peace Education, this thesis answers the questions about the suitability of videoconference as a peace education practice and the conditions that must be addressed prior to and during its potential adoption. Through examining how students, educators, and organizations utilize videoconference within an educational setting, this study adds to the existing debate of how peace education frameworks should be designed, implemented, and assessed, while also avoiding notions of cultural reproduction and powerblindness. Further, it considers how iv peace education defines dialogue and begins a discussion on whether intercultural dialogue through videoconference serves as an initial encounter within a dialogical process. Key features include: -- An examination of peace education practice and theory, which supports the construction of the Three Sphered Model of Peace Education to both design and assess peace education practices . -- Virtual and on - site field research that included schools in Tunisia, Jordan, Bahrain, and the United States, consisting of focus groups, interviews, an d videoconference observations. -- A critical analysis of the themes that emerged from virtual and on - site fieldwork, in correlation with the Three Sphered Model, as well as the distinction between dialogue and encounter.
APPROVED
Keywords: Critical Pedagogy; Peace Education; Cosmopolitanism; Constructivism; Intercultural Dialogue; Peace Studies; Videoconference